Treatment of Wastewater Associated With Crude Oil in Reservoirs - Mohammed, Thamer J.; Jasim, Jasim M. (Journal of Petroleum Research and Studies, 2019)
The produced water or wastewater resulting from the oil reservoirs in Basrah Petroleum Company / Zubair 1 Warehouse causes very high pollution in the land. The aim of this study is to find possible ways to treat such produced water and to remove turbidity through coagulation, flocculation, sedimentation and adsorption. Experimental tests of the properties for natural produced water such as turbidity, pH, TDS, TSS, and oil content found out that oil content = 137 mg/L and turbidity = 122 NTU. The produced water is treated with two types of coagulant poly aluminum chloride, alum and with two other types of adsorbent (Bentonite , Zeolite (Cation and Anion)). The coagulation, flocculation and sedimentation experiments are performed using a Jar-test device and adsorption experiments , and a magnetic stirrer device are used at different times, speeds, and concentrations. It is found through the practical results that the best dosages of (poly aluminum chloride and alum) are (3, 35, 6.75, and 30) mg/L to obtain R% (96.3, 93, 99, and 98.9), respectively. It is found from the experimental results of adsorption that the best results of weight adsorbent, stirrer time and stirrer speed to obtain maximum removal efficiency are (6 gram anion zeolite ,15 minute and 920 rpm) R% (98 , 97.8 and 99.2), respectively . It is found that the best results are poor at different parameters, except when it is used (2) gram of bentonite obtained R% of turbidity weight, stirrer time and stirrer speed by bentonite and zeolite (cation and anion) were (2 gram) . Finally, it was found that removing the oil content by adsorption (97.8) is better than coagulation (96.3). And the results for removing turbidity by coagulation (99) is better than adsorption (97.4)